PENGARUH SELF-EFFICACY LOCUS OF CONTROL TERHADAP KEPUASAN KERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL PEMODERASI PUSKESMAS AIR HAJI KABUPATEN PESISIR SELATAN - Candra, Yeki (Jurnal Ekonomi Manajemen Sistem Informasi, 2019)
Department of Management, "(Effect of Self-efficacy, Locus Of Control towards employee satisfaction of employees with organizational culture as variables moderate water clinics in South Coastal district Hajj)". This research aims to test how big the influence Of Self-efficacy, Locus Of Control towards employee satisfaction of employees with organizational culture as variables Of moderate inSouth Coastal district Hajj. Samples of this study as much as 81 and using the method of analysis of double linear reigration, Test T, Test f and coefficient of determination using SPSS 2.1The results of research obtained based on partial test (Test T) obtained: There is a significant positive influence between Self-efficacy (X1) to employee satisfaction. There is a positive but insignificant influence of the Locus Of Control (X2) against employee satisfaction. Together there is a positive and significant influence between Self-efficacy, Locus Of Control against employee satisfaction with the organization culture as a variable of moderate in the water Puskesmas Air Haji Kabupaten Pesisir Selatan.